PHYTOMELATONIN MITIGATES CADMIUM STRESS FOR BREAD WHEAT TRITICUM AESTIVUM L. - M. M. Khalid; M. H. Al-Issawi (مجلة الأنبار للعلوم الزراعية, 2024)
To elucidate the role of melatonin in mitigating the cadmium stress effect on wheat in terms of physiological and anatomical responses (e.g., root and leaf), this study was conducted in the laboratories of the College of Agriculture, University of Anbar. The aim was to investigate the important role of melatonin in alleviating Cd stress in wheat. The study included three factors: two wheat genotypes—introduced genotype G-31 (newly introduced to the country through the Iraqi Ministry of Science and Technology) and local cultivar IRAQ; four Cd concentrations (0, 75, 150, and 225 mg Cd L⁻¹ as CdCl₂); and three concentrations of melatonin (0, 100, and 200 mmole as pure melatonin). The study highlighted melatonin's role in terms of physiological and anatomical responses (e.g., root and leaf). The main results of this study confirmed the negative impact of cadmium on wheat growth, primarily affecting roots more than other plant parts. The epidermis, cortex, and vascular tissues in the xylem and phloem were negatively affected by the application of Cd. Melatonin played a vital role in boosting some physiological traits such as root growth and relative electrical conductivity. The most prominent role of melatonin was observed at the cellular level, as confirmed by the anatomical study. Melatonin helped plants cope with stress through modifications in cell organization and the thickening of either epidermal or cortical cells. Regarding the leaf, melatonin's important role was recorded in the stomatal system. More investigations are required to highlight melatonin's vital role in terms of gene expression and enzymatic and non-enzymatic antioxidants in wheat.